Controle robusto de robô paralelo baseado em compensação paralela distribuída - Grossi, Thiago Murilo (2016)
In this paper, are presented a robust control methodology based on distributed parallel compensation and models Fuzzy Takagi-Sugeno (T-S) for a planar parallel manipulator with two degrees of freedom for trajectory tracking in the space of the joints, are presente too the modeling the dynamics of the manipulator, useful for the formulation of the control law and computational simulations of the same. The modeling was performed using the equation of Lagrange, and simulated in the software Matlab/Simulink along with the two control techniques proposed. Additionally Parallel Compensation Distributed (PCD) based on Fuzzy models Takagi-Sugeno and Control Torque Computed (CTC), used for evaluation of the purposed technique. It is important noteworthy that the CTC is widely used for the control robotic manipulators, while the PCD is proposed as an alternative that requires less computing power to perform the control, since the CTC involves the calculation of the inverse dynamics of the system at every instant of time. At the end an analysis was performed to verify the efficiency of techniques used. Thus possible to observe the quality of both controllers, resulting in a small error in addition both presented the equivalent torque for performing the trajectory. It is also observed that the fuzzy control was more robust in relation to the CTC, when subjected to external forces to the system.